Pengaruh Motivasi Belajar, Minat Belajar, Kepercayaan Diri Terhadap Hasil Belajar dengan Kemampuan Kognitif Sebagai Moderasi pada Siswa Bintara Polri - Galih Risdiantoro; Rini Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aimed at learning motivation, interest in learning and self-confidence as having a significant influence on student learning outcomes, moderated by the cognitive abilities of South Kalimantan Police SPN Non-Commissioned Officer students. This research is survey research. The population of this study was 167 students who graduated from National Police Non-Commissioned Officers Batch 1 of 2023 from SPN Polda South Kalimantan. The sample in the study was taken as much as 25% of the population, so that a sample of 41.74 was rounded up to 42 people. Data analysis in research uses SMART PLS. The results of the research show that Learning Motivation, Interest in Learning and Self-Confidence have a significant influence on the Learning Outcomes of National Police Non-Commissioned Officer students at SPN Polda South Kalimantan. Apart from that, the research also found that Learning Motivation, Interest in Learning and Self-Confidence have a significant influence on Learning Outcomes, moderated by the Cognitive Ability of South Kalimantan Police SPN Non-Commissioned Officer students.